A Decolonial Theory of Religion: Race, Coloniality, and Secularity in the Americas. (10th November 2020) - Yountae, An
Abstract: This article offers a transatlantic, decolonial theory (or method for the study) of religion by insisting on the need to resituate the Americas and the transatlantic historical experience as primary sites for theorizing modern religion. Despite the surging interest in decolonial theory, its concrete connection with key topics and issues in the field of religious studies has not been systematically theorized, while decolonial theorists working outside the field of religious studies show little or no interest in the formative role of religion in the constitution of the system of modernity/coloniality. This article seeks to build a cohesive framework for a decolonial theory of religion in conversation with various decolonial, anti-racist thinkers writing from Latin American, Caribbean, and US contexts. By pointing at secularity as a key element of modernity/coloniality, the medium through which religion enacts coloniality, it raises critical questions regarding method and theory in the study of Latin American/Caribbean religions.